2021
DOI: 10.3389/fmars.2021.663278
|View full text |Cite
|
Sign up to set email alerts
|

First Insight of Meso- and Bentho-Pelagic Fish Dynamics Around Remote Seamounts in the South Atlantic Ocean

Abstract: Seamounts have long been recognised as hotspots for pelagic productivity and diversity in the world’s open ocean habitats. Recent studies have suggested that productivity may vary greatly between different seamounts, depending on complex interactions between the bathymetric features and local oceanography. These processes may enhance local primary production which support elevated biomass at higher trophic levels. In addition to enhancing local biomass, seamounts may also act as aggregative features, attractin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Previous studies have also linked the distribution and density of top order predatory fishes to prey availability [70,71]. In fact, Boaden and Kingsford [72] suggest that high densities of predators are stronger predictors of prey density than the structure and composition of habitat.…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies have also linked the distribution and density of top order predatory fishes to prey availability [70,71]. In fact, Boaden and Kingsford [72] suggest that high densities of predators are stronger predictors of prey density than the structure and composition of habitat.…”
Section: Plos Onementioning
confidence: 99%
“…This study will characterize seafloor habitats (seascapes) and the observed fish and cephalopod fauna observed during a series of ROV transects conducted on selected seamounts of the Discovery Rise. These are conspicuous and mobile components of benthic and benthopelagic megafauna that concentrate permanently or temporarily at seamounts often taking advantage of surface-originated food sources and biogenic habitats, formed by cold water corals and sponges (Auster et al, 2005;Porteiro and Sutton, 2007;Morato and Clark, 2007;Campanella et al, 2021). Recent studies have revealed that depth, seafloor habitats, local circulation processes and distribution of suspension-feeding organisms may drive fish and cephalopod species distribution in South Atlantic topographic rises (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that depth, seafloor habitats, local circulation processes and distribution of suspension-feeding organisms may drive fish and cephalopod species distribution in South Atlantic topographic rises (i.e. Rio Grande Rise, São Paulo Ridge, Tristan da Cunha seamounts) (Perez et al, 2018(Perez et al, , 2020Campanella et al, 2021). These factors contribute to habitat diversity within a single topographic feature, potentially selecting for distinctive mesoscale megafauna assemblages and affecting overall seamount diversity (e.g.…”
Section: Introductionmentioning
confidence: 99%